2015
DOI: 10.1001/jama.2015.13744
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Cardiovascular Responses to Energy Drink Consumption in Healthy Adults

Abstract: Author Contributions: Drs Sammon and Trinh had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 6 publications
3
37
1
Order By: Relevance
“…This controversial observation could be due to differences between the EDs in terms of the amounts of caffeine (;114 compared with 240 mg) and sugar (;39 compared with ;62 g) (i.e., 355 mL of a sugared Red Bull used in our study compared with 480 mL of a sugared Rockstar ED). However, taking into account that we observed a gradual blood pressure increase with peak responses between 80 and 100 min postconsumption (17), it is possible that peak blood pressure responses in the study by Svatikova et al (21) could not be reached within the 30-min measurement period. Thus, unless the assessment of cardiovascular responses to EDs is conducted over periods of $60 min, there is a high risk of 1) false-negative results and 2) the possibility of underestimating their real cardiovascular impact (39,40).…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 58%
See 3 more Smart Citations
“…This controversial observation could be due to differences between the EDs in terms of the amounts of caffeine (;114 compared with 240 mg) and sugar (;39 compared with ;62 g) (i.e., 355 mL of a sugared Red Bull used in our study compared with 480 mL of a sugared Rockstar ED). However, taking into account that we observed a gradual blood pressure increase with peak responses between 80 and 100 min postconsumption (17), it is possible that peak blood pressure responses in the study by Svatikova et al (21) could not be reached within the 30-min measurement period. Thus, unless the assessment of cardiovascular responses to EDs is conducted over periods of $60 min, there is a high risk of 1) false-negative results and 2) the possibility of underestimating their real cardiovascular impact (39,40).…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 58%
“…The potential importance of the volume of the ED ingested on the cardiovascular system may also be underscored by the observation that the increases in systolic and diastolic blood pressures in response to 355 mL of Red Bull in our study (17) were ;2 mm Hg less than those reported in the study by Steinke et al (30) in response to 500 mL of an ED with a composition similar to that of Red Bull. This contention is further substantiated by findings from Svatikova et al (21) in which 480 mL of a Rockstar ED, containing 240 mg caffeine and ;62 g sugar, substantially elevated blood pressure 30 min after ingestion. Furthermore, Passmore et al (41), in their investigation in healthy male subjects of cardiovascular and renal effects of increasing oral doses of caffeine, observed a linear dose-response relation for systolic blood pressure, a finding that is in agreement with the aforementioned studies in which increasing volume loads, and therefore increasing amounts of caffeine, affected blood pressure.…”
Section: Eds and Hemodynamics: Discrepancies Between Studiesmentioning
confidence: 79%
See 2 more Smart Citations
“…For example, trials have shown acute cardiovascular effects of energy drinks, particularly among those at higher risk for such events. 17,18 Case reports have linked energy drink consumption with serious adverse events, such as stroke, 19 seizures [20][21][22] and serious cardiac effects. [23][24][25][26][27] Data from emergency department visits have also identified adverse outcomes associated with energy drinks.…”
mentioning
confidence: 99%